Reliability and credibility analysis of Inlow’s 60 second diabetic foot screening tool for diabetic foot risk stratification and its feasibility in India: a systematic review - Parasuraman, Madhivadhanam; Giridharan, Bhanumati; Vijayalakshmi, G. (International Surgery Journal, 2017)
Diabetes is the common cause for amputation of lower limb. Foot ulcers and associated complications are important causes of mortality and morbidity in patients with diabetes. Hence, it is important to predict diabetic foot ulcer in its early stages to eliminate the risks of foot amputation. Inlow’s 60 second diabetic foot ulcer screening tool is gaining immense attention over the years which is associated with its simplicity to use, rapid detection of high risk diabetic feet, and provides referral for patients necessitating treatment. A systematic review is conducted to assess the reliability and credibility of using Inlow’s 60 second diabetic foot screening tool for diabetic foot risk stratification and to examine its feasibility in the Indian context. Eight studies suited the inclusion criteria which were analysed systematically. The findings of the paper reveal that the sixty second tool acts as a better tool for diabetic foot ulcer risk stratification; however, modifications are necessary for its application in the Indian context.